1996
DOI: 10.1126/science.274.5290.1167
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Vortex Dynamics in Superconducting Films with Regular Arrays of Defects

Abstract: The microscopic mechanism of the matching effect in a superconductor, which manifested itself as the production of peaks or cusps in the critical current at specific values of the applied magnetic field, was investigated with Lorentz microscopy to allow direct observation of the behavior of vortices in a niobium thin film having a regular array of artificial defects. Vortices were observed to form regular and consequently rigid lattices at the matching magnetic field, at its multiples, and at its fractions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
412
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(437 citation statements)
references
References 18 publications
23
412
2
Order By: Relevance
“…There are other examples of particles moving over ordered substrates, such as vortices in type-II superconductors with periodic pinning arrays [41][42][43] or colloids placed on optically created periodic substrates 44,58 . In these systems the dynamics is overdamped; however, there can be directional locking effects in which the particles preferentially move along symmetry directions of the underlying substrate as the direction of drive is rotated with respect to the substrate lattice [45][46][47][48][49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
“…There are other examples of particles moving over ordered substrates, such as vortices in type-II superconductors with periodic pinning arrays [41][42][43] or colloids placed on optically created periodic substrates 44,58 . In these systems the dynamics is overdamped; however, there can be directional locking effects in which the particles preferentially move along symmetry directions of the underlying substrate as the direction of drive is rotated with respect to the substrate lattice [45][46][47][48][49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
“…The ground state of the system is obtained by simulating field-cooled experiments [18]. We now consider a disk containing, e.g., 8 vortices in the field h = 15 (for R =1.5µm, this corresponds to H ≈ 45Oe).…”
mentioning
confidence: 99%
“…It has been found that a periodic pinning landscape 1-11 leads to strong commensurability effects which appear when the number of vortices equals an integer (n) multiple of the number of pinning sites (i.e., at fields H = nH 0 with H 0 the first matching field where the number of vortices equals the number of pins), resulting in peaks in, e.g., the critical current as a function of applied magnetic field. However, at larger magnetic fields the pinning centers become repulsive potentials for the incoming vortices, resulting in excess vortices, located preferentially at the interstitial sites between the pinning centers, forming different type of ordered vortex configurations [12][13][14][15][16] . The interstitial vortices can be highly mobile and lead to strong reduction of the critical parameters of the system.…”
mentioning
confidence: 99%